A unified analytical method calculating brittle rocks deformation induced by crack growth. (January 2019) - Li, Xiaozhao; Qu, Xiaolei; Qi, Chengzhi; Shao, Zhushan
Abstract: An improved unified method is proposed to calculate the relations of stress to axial, lateral, and volumetric strains, involving the short-term progressive failure and long-term creep of brittle rocks. In the present paper, wing crack model, subcritical crack growth law and a crack-strain criterion for brittle rocks are coupled to formulate the frame of the proposed method. The limitation of the crack growth at crack coalescence is discussed as well, and the effects of confining pressure on relations between axial, lateral and volumetric strains and axial stress during progressive failure are analyzed, then the corresponding stress-strain curve during multi-loading creep is obtained. These theoretical derivations and calculation agree well with the previous experimental results, the proposed unified method is validated and can be applied into calculate brittle rocks deformation induced by crack growth.